Influence of Functional Capacity Evaluation on Physician's Assessment of Physical Capacity of Veterans With Chronic Pain: A Retrospective Analysis. Issue 7 (22nd October 2016) - Peppers, Dominique; Figoni, Stephen F.; Carroll, Breda W.; Chen, Michael M.; Song, Sungchan; Mathiyakom, Witaya
Abstract: Background: Physicians have difficulty predicting patients' occupational limitations, abilities, and success from clinical evaluation (CE) of pathology and impairments, especially in the presence of chronic pain. Additional information from a functional capacity evaluation (FCE) may improve the accuracy of their physical capacity assessments. It is not known whether FCE information will change these assessments. No such study has been published using Veterans or non‐Veterans. Objective: To determine the influence of FCE data on the physician's assessment of the US Department of Labor's Dictionary of Occupational Titles (DOT) work capacity levels of Veterans with chronic moderate‐intensity pain. Design: Retrospective analysis. Setting: Tertiary care medical center. Participants: Veterans aged 18‐60 years with moderate chronic musculoskeletal pain who were seeking employment. Methods: Two kinesiotherapists performed FCEs on all participants, namely, the lumbar protocol of the EvalTech Functional Testing System (BTE, Inc, Hanover, MD). One physiatrist performed CEs in all participants. Two other physiatrists assessed DOT physical capacity levels using CE data alone and later using combined CE and FCE data. Main Outcome Measurements: DOT physical capacity level (sedentary = 1, light = 2, medium = 3, heavy = 4, very heavy = 5). Results: Of 55 charts reviewed, 27 met inclusion/exclusion criteria. The mean age was 38 years, and there were 25 male and 2 female participants. The predominant pain location was the lower back. DOT scores for 2 physicians were averaged. The mean ± SD DOT scores for CE only and CE+FCE conditions were 2.04 ± 0.33 and 2.40 ± 0.90, respectively. In all, 65% of DOT scores changed (17% decreased and 48% increased at least 1 level) after FCE data were considered. A 1‐sample t test revealed that the mean CE+FCE DOT score was significantly greater than the mean CE‐only score (by 20%, P = .02). Interrater agreement (weighted κ) for CE+FCE‐based DOT scores was much higher than for CE alone (0.715 versus 0.182). Conclusion: The addition of FCE data to CE changed the majority of physician‐assigned DOT levels. FCE significantly increased the mean DOT physical work capacity level provided by the physician to Veterans with chronic moderate‐intensity pain, especially if the initial assessment was designated as "light." FCE may facilitate a more objective and accurate determination of Veterans' work capacity. Level of Evidence: III